Perilaku Remaja Atas Pengasuhan Ayah (Studi Kasus) di Jorong Parik Putuih Kenagarian Ampang Gadang Ampek Angkek Agam - Hartati, Sri (PT. ALHAFI BERKAH INDONESIA, 2023)
Father involvement in parenting is more than just having positive interactions with their children, but also paying attention to the child's development. Parenting with these characteristics involves the ability to understand the child's condition and needs, the ability to choose the most appropriate response both affectively, cognitively, and emotionally. Busy working wives demand fathers to look after and care for their children. The goal to be achieved in this study is to find out the form of parenting that is carried out by fathers towards adolescent children in the family. This research is descriptive qualitative in nature, namely a method that describes the conditions that occur in the field in the form of words or not in the form of numbers. The informants in this study consisted of key informants, fathers and adolescent children, as well as supporting informants, namely mothers and aunts in this family. The results obtained from research through interviews and observations obtained an overview of the supervision carried out by the father, namely the father gave too much freedom to the child without certain norms that had to be followed, paid little attention to disciplinary factors and prioritized the will of the child, the child was free to choose in terms of what they want, children are free to act as they wish. Fathers in this case tend to give more freedom to children both in sosializing and behaving without strict supervision, allowing their children to make mistakes, and keeping children away from coercion, obligation, punishment and being reluctant to correct children's behavior deviations.